Analysis of cognitive function and its related factors after treatment in Meniere’s disease - Zhong, Jiake; Li, Xin; Xu, Jia; Chen, Wenjing; Gao, Juanjuan; Lu, Xingxing; Liang, Sichao; Guo, Zhenping; Lu, Manlin; Li, Yunshuo; Yi, Haijin (Frontiers in Neuroscience, 2023)
A growing body of research recently suggested the association between vestibular dysfunction and cognitive impairment. Meniere’s disease (MD), a common clinical vestibular disorder, is usually accompanied by hearing loss and emotional stress, both of which may mediate the relationship between vestibule dysfunction and cognition. It is currently unknown whether the cognitive decline in MD patients could improve through treatment and how it relates to multiple clinical characteristics, particularly the severity of vertigo. Therefore, in the present study, the MD patients were followed up for 3, 6, and 12 months after treatment, and the cognitive functions, vertigo symptoms, and related physical, functional, and emotional effects of the patients were assessed using the Montreal Cognitive Assessment (MoCA) and Dizziness Handicap Inventory (DHI), aiming to explore the change in cognition before and after therapy and the correlation with various clinical features. It was found that cognitive decline in MD patients compared to healthy controls before therapy. Importantly, this cognitive impairment could improve after effective therapy, which was related to the severity of vertigo, especially in functional and physical impacts. Our results support the view that vestibular dysfunction is a potentially modifiable risk factor for cognitive decline.